Opportunity of Integrated Sustainable Tourism - Sadikin, Pipin Noviati (Prasetiya Mulya Publishing, 2023)
Urbanization led to the extension of the administrative boundaries of the city of Bogor to the villages border in Bogor Regency. This process forms physical, social, and economic interactions between cities and villages, including creating integrated tourism opportunities between cities and districts. However, there are many challenges faced, including the packaging of tourist attractions, weak management of tourism destinations, disparities in the development of tourism areas, and others. This study aims to identify the potential and challenges of sustainable tourism, ecotourism, and urban tourism that are integrated within the framework of city and district linkages; and strategic issues that can become opportunities for development planning. The research method used qualitative descriptive analysis with research objects on opportunities and attractions of sustainable tourism, ecotourism or urban tourism (urban tourism), and amenities in Bogor City and Bogor Regency, which are analyzed using the five pillars of sustainable.